Psychological effects of water scarcity on community members: a case study of Lephalale municipality, Limpopo province, South Africa - Seretlo-Rangata, Mmakwena Linda; Sodi, Tholene; Govender, Saraswathie (Frontiers in Psychology, 2025)
IntroductionWater is essential for human survival and serves various purposes, including domestic, socioeconomic, and agricultural activities. However, water scarcity has emerged as a significant threat to this vital resource, posing a global challenge. While discussions surrounding the consequences of water scarcity typically emphasizes its effects on physical health and socioeconomic impacts, the mental and psychological effects on communities are often overlooked. Thus, the study aimed to explore the psychological effects of water scarcity on community members in Lephalale municipality, Limpopo province, South Africa.MethodsA qualitative research approach was used in the study. Participants were selected using purposive sampling and twenty participants who relied mainly on communal taps to access water were included (10 males and 10 females). Semi-structured in-depth interviews were used to collect data and interviews were audio recorded and later transcribed and translated by a language expert. Data were analyzed using content thematic analysis.ResultsThree main themes emerged from the study results: (1) emotional distress; (2) interpersonal conflicts; (3) disruptions in the activities of daily living. Emotional distress included feelings of shame, embarrassment, anger, disappointment, hopelessness and helplessness. Additionally, interpersonal conflicts arose due to competition for water resources, and disruptions in daily activities were linked to water access challenges.ConclusionThe study findings demonstrated that water scarcity has a significant psychological impact on community members. The study concludes by recommending the integration of psychological principles and involvement of mental health care practitioners when developing water management programmes, strategies, interventions, and policy. The study can provide policy makers and mental health care practitioners valuable insights into the mental health challenges faced by communities affected by water scarcity. Moreover, these study findings can assist mental health care practitioners to tailor their interventions to address the specific needs of communities experiencing water scarcity, particularly community members presenting with mental health challenges associated with this issue.